Perlindungan Hukum terhadap Konsumen dalam Kontrak Bisnis Properti - Rikky Nelson Manurung; I Made Kantikha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Property business is the activity of buying and selling a plot of land or house involving 2 (two) parties between the seller (business actor) and the buyer (consumer), in its implementation gives birth to legal relationships carried out through agreements. Quality in running a property business, business actors selling their plot of land to consumers are inseparable from the fact that the business actor gets the land previously from the landowner to then sell it to consumers. The method used in this study is Normative Juridical. The legal protection of agreements made by business actors and consumers in the property business is guided by articles 1320 and 1338 of the Civil Code. Breach of promise not to carry out the agreed is a form of default committed by one of the parties to the agreement as regulated by article 1234 of the Civil Code which can be resolved with a